Zhengica cornuta gen. nov., sp. nov., a new genus and species of Pentatomidae from East Asia (Hemiptera: Heteroptera) - Rédei, Dávid; Tsai, Jing-Fu (Zootaxa, 2021)
Zhengica cornuta gen. nov., sp. nov. (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Pentatomini) from Shanxi, China, is described, illustrated, and its phylogenetic affinities are discussed. The genus is recognized as a generalized member of the clade of Pentatoma Olivier, 1789 and related genera, its phylogenetically closest relative is probably Cervicoris Hsiao & Cheng, 1977.